Ductular Reaction Cells Display an Inflammatory Profile and Recruit Neutrophils in Alcoholic Hepatitis. Issue 5 (12th March 2019) - Aguilar‐Bravo, Beatriz; Rodrigo‐Torres, Daniel; Ariño, Silvia; Coll, Mar; Pose, Elisa; Blaya, Delia; Graupera, Isabel; Perea, Luis; Vallverdú, Júlia; Rubio‐Tomás, Teresa; Dubuquoy, Laurent; Armengol, Carolina; et al.
Abstract : Chronic liver diseases are characterized by the expansion of ductular reaction (DR) cells and the expression of liver progenitor cell (LPC) markers. In alcoholic hepatitis (AH), the degree of DR expansion correlates with disease progression and short‐term survival. However, little is known about the biological properties of DR cells, their impact on the pathogenesis of human liver disease, and their contribution to tissue repair. In this study, we have evaluated the transcriptomic profile of DR cells by laser capture microdissection in patients with AH and assessed its association with disease progression. The transcriptome analysis of cytokeratin 7‐positive (KRT7 + ) DR cells uncovered intrinsic gene pathways expressed in DR and genes associated with alcoholic liver disease progression. Importantly, DR presented a proinflammatory profile with expression of neutrophil recruiting C‐X‐C motif chemokine ligand (CXC) and C‐C motif chemokine ligand chemokines. Moreover, LPC markers correlated with liver expression and circulating levels of inflammatory mediators such as CXCL5. Histologically, DR was associated with neutrophil infiltration at the periportal area. In order to model the DR and to assess its functional role, we generated LPC organoids derived from patients with cirrhosis. Liver organoids mimicked the transcriptomic and proinflammatory profile of DR cells. Conditioned medium from organoids induced neutrophil migration and enhanced cytokine expression in neutrophils. Likewise, neutrophils promoted the proinflammatory profile and the expression of chemokines of liver organoids. Conclusion : Transcriptomic and functional analysis of KRT7 + cells indicate that DR has a proinflammatory profile and promote neutrophil recruitment. These results indicate that DR may be involved in the liver inflammatory response in AH, and suggest that therapeutic strategies targeting DR cells may be useful to mitigate the inflammatory cell recruitment in AH.